Wood Chip Biochar–Sepiolite Composite Reduces Cadmium Accumulation in Maize - Trinh Tu Anh; Nguyen Thi Xuyen; Le Thi Hien; Do Dat (Tropical Aquatic and Soil Pollution, 2026)
This study aimed to evaluate the effectiveness of a composite material consisting of wood chip biochar (WCB) and sepiolite in reducing cadmium (Cd) uptake, accumulation, and translocation in maize cultivated in Cd-contaminated soil in Vietnam. A field experiment was conducted using three maize varieties (LVN10, NK7328, and CP511) under eight treatment conditions, including a control (CK), individual applications of WCB or Sep, and combined WCB/Sep treatments at different ratios. Cadmium concentrations in roots, stems, leaves, and grains were determined using atomic absorption spectroscopy (AAS), while the bioconcentration factor (BCF) and translocation factor (TF) were calculated to assess Cd accumulation and transport within the plants. The results showed that Cd accumulated predominantly in the roots, followed by leaves, stems, and the lowest levels in grains. Individual application of WCB or Sep only resulted in limited reductions in Cd accumulation, whereas the combined treatments exhibited more pronounced effects. Among them, the W2S2 treatment (0.2% WCB + 0.6% Sep) demonstrated the highest effectiveness across most parameters, significantly reducing Cd concentrations in roots, stems, leaves, and grains compared with the control. The BCF values decreased by up to 36.1% in LVN10 and 45.0% in CP511, while all TF values remained below 1, indicating restricted Cd translocation into grains. These findings demonstrate that the WCB/Sep composite has strong potential as an effective immobilization strategy to reduce the bioavailability of Cd in soil, thereby improving crop safety and supporting the sustainable management of heavy metal-contaminated agricultural land.